Digital Brand Transaction Model of Halal Products in the Urban Consumer Society - Rohmah, Ichmi Yani Arinda; Munandar, Aris (Indonesian Journal of Digital Society is a scientific journal, 2020)
This study examines the form of digital transaction models on halal products that are the needs of the people of South Jakarta in the era of technology-based markets today. Digital era is closely related to the efficiency and effectiveness of time in meeting the needs of people's lives which are fast and easy. Through digital markets the community is facilitated in meeting all the necessities of life. This makes the digital market a space for meeting the needs that are visited by many people. Excess digital market space provides a great opportunity for the community to become independent business actors. Besides that, the digital market still has many shortcomings that need attention. Various types of digital market features framed in the form of applications on community gadgets have an effect on the performance of products that are said to be halal or not halal, both in terms of the legality of goods sold, compliance with product requirements is said to be halal, to the services of buying and selling products in the digital market. Keywords : Transactions, digital, halal products, consumptive, urban society, South Jakarta.